2020
DOI: 10.1364/oe.387939
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous photodiodes on silicon nitride waveguides

Abstract: Heterogeneous integration through low-temperature die bonding is a promising technique to enable high-performance III-V photodetectors on the silicon nitride (Si3N4) photonic platform. Here we demonstrate InGaAs/InP modified uni-traveling carrier photodiodes on Si3N4 waveguides with 20 nA dark current, 20 GHz bandwidth, and record-high external (internal) responsivities of 0.8 A/W (0.94 A/W) and 0.33 A/W (0.83 A/W) at 1550 nm and 1064 nm, respectively. Open eye diagrams at 40 Gbit/s are demonstrated. Balanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In terms of signal coherence, recent studies have shown that the phase noise of the soliton repetition frequency at 10's of GHz can be orders of magnitude smaller than that of its pump laser 5,[19][20][21] . When microresonator solitons are married with integrated lasers 22,23 , amplifiers 24 , and high-speed photodiodes 25 through heterogeneous or hybrid integration, a fully integrated mmWave platform can be created with high-power, high-coherence performance, and the potential for large-scale deployment through mass production ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of signal coherence, recent studies have shown that the phase noise of the soliton repetition frequency at 10's of GHz can be orders of magnitude smaller than that of its pump laser 5,[19][20][21] . When microresonator solitons are married with integrated lasers 22,23 , amplifiers 24 , and high-speed photodiodes 25 through heterogeneous or hybrid integration, a fully integrated mmWave platform can be created with high-power, high-coherence performance, and the potential for large-scale deployment through mass production ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…2b ). These elements interface with a frequency doubler (SHG) including a polarization rotator and a photodetector array that are heterogeneously integrated 33 , 39 , 42 , 52 . The output of the octave-spanning Si 3 N 4 comb chip is directed to two cascaded dichroics that spectrally filter the microcomb into three key spectral bands, a long and a short wavelength band near 2 and 1 μm, respectively, separated by an octave, and the center band near 1.55 μm.…”
Section: Resultsmentioning
confidence: 99%
“…However, to realize these integrated microcomb-based systems, integrated photonic interposers that connect and operate on optical signals that transit between the many constituent photonic components will be critical. In fact, the pursuit of such integrated systems has driven recent progress in active photonics, e.g., lasers 29 32 and detectors 33 , nonlinear photonics in microresonators 5 – 9 , 34 , 35 and waveguides 36 39 , and passive photonics and heterogeneous integration 40 42 , and has motivated milestones such as the generation of microcombs using chip-scale lasers 43 45 . Photonic interposers that collect, filter, route, and interface light between many such active and passive devices are essential to realize the improvements in cost, size, weight, and power, performance, and scalability, offered by microcombs and integrated photonics, and will promote further system-level innovation using frequency combs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the platforms mature, additional functionality is being added besides the commonly available heaters/phase shifters. Recently, Lionix demonstrated the co-integration of an InP gain chip for 1550 nm through butt-coupling [7] and Ligentec showed wafer-bonding-based integration of PDs for 1550 nm as well [8]. However, a lack of integrated light sources and detectors remains for wavelengths other than the telecom range.…”
Section: Introductionmentioning
confidence: 99%